Effects of experimentally increased in ovo lysozyme on egg hatchability, chicks complement activity, and phenotype in a precocial bird - Javůrková, Veronika; Krkavcová, Eva; Kreisinger, Jakub; Hyršl, Pavel; Hyánková, Ludmila (Journal of experimental zoology. Part A, Ecological genetics and physiology, 2015)
In birds, spectrum of egg white proteins deposited into the egg during its formation are thought to be essential maternal effects. Particularly, egg white lysozyme (LSM), exhibiting great between and within species variability, is considered to be essential for developing avian embryos due to its physiological, antimicrobial, and innate immune defense functions. However, there have been few studies investigating effects of LSM on early post-hatching phenotype, despite its broad physiological and protective role during embryogenesis. Here, we test how experimentally increased concentrations of egg white LSM affect hatchability in Japanese quail (Coturnix japonica) and chick phenotype immediately after hatching (particularly body weight, tarsus length, plasma LSM concentration, and plasma complement activity). Chicks from eggs with increased LSM concentration displayed reduced tarsus length compared to chicks from control eggs while hatchability, body weight and plasma LSM concentration were unaffected. It is worth noting that no effect of increased in ovo lysozyme on eggs hatchability could be related to pathogen-free environment during artificial incubation of experimental eggs causing minimal pressure on embryo viability. While tangible in vivo mechanisms during avian embryogenesis remain to be tested, our study is the first to document experimentally that egg white LSM appears to have growth-regulation role during embryo development, with possible underlying phenotypic consequences in the early post-hatching period in precocial birds.
Keywords: Ovum; ovum; fenotyp; vaječný bílek; Phenotype; Embryonic Development; tarzus u zvířat; Body Weight; komplement; Complement System Proteins; Animals; Egg White; Muramidase; zvířata; embryonální vývoj; Tarsus, Animal; tělesná hmotnost; muramidasa; Coturnix